Correlation of Cardiac Troponin I with Left Ventricular Systolic Function in Patients with Acute ST-segment Elevated Myocardial Infarction (Faridpur Medical College Journal, 2021)
Myocardial infarction is one of the leading cause of death globally and following acute myocardial infarction prognosis depends on extent of myocardial damage. This study was aimed to correlate cardiac troponin I level with the left ventricular systolic function in patients with acute ST-elevated myocardial infarction. A total of 104 patients of acute ST-segment elevated myocardial infarction receiving streptokinase therapy within 12 hours of onset of chest pain were studied. Cardiac troponin I concentration was measured by immunometric assay and echocardiographic left ventricular ejection fraction was calculated by modified biplane Simpson's method. Left ventricular ejection fraction (LVEF) was compared with serum cardiac troponin I concentration. Study subjects were divided into two groups on the basis of LVEF. In group I, there were 54 patients with LVEF < 50% and in group II, there were 50 patients with LVEF >_ 50%. The mean cTnI within 12 hours of onset was 129 ± 8.7 ng/ml in group I and11 ± 2.1 ng/ml group II and the difference was statistically significant (p_ 6.6 ng/ml provided a good indication for LVEF